2022
DOI: 10.20473/mgi.v17i1.70-75
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake, Food Purchasing Access, and Stress During the Covid-19 Pandemic: A Descriptive Study Among College Students of Jenderal Soedirman University

Abstract: The COVID-19 pandemic is causing social restrictions that leads to school form home. Long period of online learning system will likely make excessive food intakes and adolescent would try popular diet, got high stress due to staying at home for a long period of time, and decreased of food purchasing access. This study aimed to describe the food intakes, food purchasing access, and stress level among college students of Jenderal Soedirman University during pandemic period. This study was crossectional design st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…These perspectives are supported by other studies on the consumption of away-from-home foods during the COVID-19 pandemic in Indonesia. In a survey on dietary behaviors of college students in Indonesia studying from home during COVID-19, authors found an increase in the option of buying cooked food from online delivery services [ 46 ]. Another quantitative study among college students in Indonesia showed no significant decrease in consumption of packaged foods and sugar sweetened beverages during the pandemic in August 2020 compared to December 2019 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…These perspectives are supported by other studies on the consumption of away-from-home foods during the COVID-19 pandemic in Indonesia. In a survey on dietary behaviors of college students in Indonesia studying from home during COVID-19, authors found an increase in the option of buying cooked food from online delivery services [ 46 ]. Another quantitative study among college students in Indonesia showed no significant decrease in consumption of packaged foods and sugar sweetened beverages during the pandemic in August 2020 compared to December 2019 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%